The Role of Customer in Risk Prevention and Complaint Handling in Banking - Adrian Dewa Mutiara Sakti; Tri Hutomo Yogiantoro; Nasha Aurellya Putri Intiati; Ida Ayu Nuh Kartini (Universitas Kristen Cipta Wacana, 2026)
The banking sector relies heavily on service quality to maintain public trust and financial stability. This study analyzes the strategic role of customer service in risk prevention and complaint handling at Bank Jatim, a regional development bank in East Java. Using a qualitative descriptive approach, data were collected through in-depth interviews with customer service officers and documentation reviews. The research focuses on identifying the types of customer complaints, the procedures for handling them, and the role of customer service as a frontline defense against operational and reputational risks. The findings reveal that the most frequent complaints relate to transaction failures, such as ATM cash withdrawals and real-time transfers. Customer service officers mitigate operational risks by verifying data accuracy and ensuring compliance with standard operating procedures (SOPs). Furthermore, they prevent reputational risks through empathetic communication and transparent complaint resolution. The study concludes that customer service is not merely a support function but an integral component of the bank's risk management system, contributing significantly to customer trust and operational stability.